2019
DOI: 10.4196/kjpp.2019.23.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Far-infrared radiation stimulates platelet-derived growth factor mediated skeletal muscle cell migration through extracellular matrix-integrin signaling

Abstract: Despite increased evidence of bio-activity following far-infrared (FIR) radiation, susceptibility of cell signaling to FIR radiation-induced homeostasis is poorly understood. To observe the effects of FIR radiation, FIR-radiated materials-coated fabric was put on experimental rats or applied to L6 cells, and microarray analysis, quantitative real-time polymerase chain reaction, and wound healing assays were performed. Microarray analysis revealed that messenger RNA expressions of rat muscle were stimulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Microarray data extracted from a previous study [ 23 ] were assembled for GO map analysis. We confirmed that pathways related to glucose transport and regulation were stimulated by FIR in rat skeletal muscle ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microarray data extracted from a previous study [ 23 ] were assembled for GO map analysis. We confirmed that pathways related to glucose transport and regulation were stimulated by FIR in rat skeletal muscle ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, microarray analysis revealed that mRNA expression in rat muscle cells was stimulated by FIR radiation in a dose-dependent manner at 10% and 30% BMCF [ 23 ]. Additional analysis of genetic data through GO analysis confirmed the possibility that FIR could affect glucose metabolism ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIR therapy also enhances HO-1 synthesis, activates eNOS, inhibits vessel endothelium growth, reduces oxidative vessel sclerosis, and improves vessel repair effects (Chang, 2018;Choi et al, 2016;Lin et al, 2016). Chang (2018) and Lee et al (2019) also mentioned that FIR treatment can reduce and delay IL-6 and TNF-a responses, which may improve vascular endothelial cell function and help reduce the inflammatory response. In the present study, we found that DPA pulse strength; DPA blood flow strength; soreness, tingling, and coldness in the foot; right foot pain; and sensitivity to tactility and pressure improved significantly in the experimental group after 6 months of FIR therapy, suggesting that the intervention may have eased the acute-phase inflammatory response or promoted healing of peripheral arterial occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research has shown that FIR therapy reduces atherosclerosis in humans (Chen, Lee, et al, 2016;Chen, Yang, et al, 2016;Choi et al, 2016;Lo et al, 2019;Yu et al, 2006). Due to FIR's ability to increase vasodilation, improve vascular endothelial cell function, slow the inflammatory response, and reduce endothelial oxidative stress in addition to evidence that it stimulates skeletal muscle cell migration mediated by platelet-derived growth factor and tissue healing (Lee et al, 2019), clinicians have used such treatment widely to treat hemodialysis fistulas (Lee et al, 2019).…”
mentioning
confidence: 99%